KEEFEKTIFAN KONSELING KELOMPOK DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS X PM DI SMK NEGERI 3 PONTIANAK - Felagia Indata; Yuline; Amallia Putri (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2023)
This study aims to determine how effectively career information services aid in the planning of students' careers. In this study, a pre- and post-test design with one group was employed in the pre- experimental design process. 261 eighth-grade SMPN 2 Sungai Raya students took part in the study. A straightforward, methodical checking strategy makes it possible to check using testing. 40 pupils were therefore selected in this study as examples. Only 60.80% of students were planning careers according to the study's findings before students began receiving career information services; however, this number increased to 78.59% after students began receiving such services. It may be inferred from the outcomes of the Effect Size t test with a Cohen’s d 2.35 that